Stable in vitro fluorescence for enhanced live imaging of infection models for Batrachochytrium dendrobatidis. - Rebecca J Webb; Andrea L Vu; Lee F Skerratt; Lee Berger; Francisco De Jesús Andino; Jacques Robert (PLoS ONE)
Realistic and modifiable infection models are required to study the pathogenesis of amphibian chytridiomycosis. Understanding the mechanism by which Batrachochytrium dendrobatidis (Bd) can infect and kill diverse amphibians is key to mitigating this pathogen and preventing further loss of biodiversity. In vitro studies of Bd typically rely on a tryptone based growth media, whereas the recent development of a kidney cell-line infection model has provided a more realistic alternative, without the need for live animals. Here we use expression of a fluorescent reporter to enhance the in vitro cell-line based growth assay, and show that transformed Bd cells are able to invade and grow in an amphibian kidney epithelial cell line (A6) as well as in a new system using a lung fibroblast cell line (DWJ). Both Bd and host cells were modified to express reporter fluorescent proteins, enabling immediate and continuous observation of the infection process without the need for destructive sampling for fixation and staining. Plasmid DNA conferring hygromycin resistance and TdTomato (RFP) expression was delivered to Bd zoospores via electroporation, and continuous antibiotic selection after recovery produced stable fluorescent Bd transformants. Host cells (A6 and DWJ) were transfected before each assay using lipofection to deliver plasmid DNA conferring green fluorescent protein (GFP) and containing an empty shRNA expression cassette. Bd RFP expression allowed easy localisation of fungal cells and identification of endobiotic growth was assisted by host GFP expression, by allowing visualization of the space in the host cell occupied by the invading fungal body. In addition to enabling enhanced live imaging, these methods will facilitate future genetic modification and characterisation of specific genes and their effect on Bd virulence.